2022
DOI: 10.1108/ilt-08-2021-0295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cutting parameters on tool life during end milling of AISI 4340 under MQL condition

Abstract: Purpose The purpose of this paper is to study the cutting performance of high-speed regime end milling of AISI 4340 by investigating the tool life and wear mechanism of steel using the minimum quantity lubrication (MQL) technique to deliver the cutting fluid. Design/methodology/approach The experiments were designed using Taguchi L9 orthogonal array with the parameters chosen: cutting speed (between 300 and 400 m/min), feed rate (between 0.15 and 0.3 mm/tooth), axial depth of cut (between 0.5 and 0.7 mm) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…68 Infrared thermography of cutting temperature during run nos. 5,6,8,12,18,20,23,25, and 27 are shown in Supplemental Figure 7. The cutting temperature rises as the cutting speed increases as in 80-260 m/min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…68 Infrared thermography of cutting temperature during run nos. 5,6,8,12,18,20,23,25, and 27 are shown in Supplemental Figure 7. The cutting temperature rises as the cutting speed increases as in 80-260 m/min.…”
Section: Resultsmentioning
confidence: 99%
“…Enterprises may develop a solid rapport with society and depart a good business impression on people by making use of these benefits and beneficial consequences. 5 Dry machining is attracting more investigation due to its environmental advantages. The generation of high temperature in the dry cutting condition with hard machining may impair the desired tool qualities, resulting in the production of built-up layers and edges.…”
Section: Introductionmentioning
confidence: 99%
“…( 9), D C is the drag coefficient which uses the spherical drag coefficient model [31], as shown in Eq. (10).…”
Section: Establishment Of Nozzle Model and Cfd Numerical Simulationmentioning
confidence: 99%
“…Çamlı, et al [9] focused on the influence of MQL in the machining of steel parts for rail wheels, results showed that the MQL can reduce the surface roughness and tool wear. Ahmad, et al [10] researched the tool life and wear mechanism of milling AISI 4340, and showed that the tool life was increased and tool wear was reduced when machining with MQL. Jiang, et al [11] researched the effect of cutting parameters on average surface roughness in MQL, wet and dry cutting, and found that the surface roughness under MQL cutting condition was the best.…”
Section: Introductionmentioning
confidence: 99%
“…But, in the actual scenario, dry machining is less effective in difficult-to-machine alloys when more tool life and a high surface finish are in demand (Gupta et al , 2022). In these circumstances, machining using the minimum quantity lubrication (MQL) approach has proven to be a practical alternative for traditional (flood) and dry cutting conditions (Vadnere and Kalpande, 2023). In comparison to flooded machining (30,000–60,000 ml/h), MQL technology accurately lubricates the machining zone with a focused, high-velocity jet that uses only 10–100 ml/h of cutting fluid (Dubey and Sharma, 2023).…”
Section: Introductionmentioning
confidence: 99%